PENGARUH INFORMASI AKUNTANSI KEUANGAN PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN- PERUSAHAAN INDUSTRI PERDAGANGAN, JASA DAN INVESTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA UNTUK TAHUN 2008 HINGGA 2016 - Onasis, Dini (Komunitas Manajemen Kompetitif, 2018)
The purpose of establishing a company is to gain the maximum profit. The next goal is to prosper shareholder value. One of the tools that a company uses to achieve its objectives is financial accounting called Financial statements. The financial statements also indicate what management has done (stewardship), or Management's accountability of the resources entrusted to it. Users of financial statements want to assess what has been done by management or accountability what management does to the resources entrusted to it. Accounting information from the financial statements can describe the condition of the company. In this study examine the market reaction of information received by the public (Investor) on stock prices. If the information presented reports success in performance then the market will respond positively and if the performance fails then the market will respond negatively with the company's stock price decline presented. Researchers examine the influence of information revealed by the company on its Financial Statement to their share price, where the information used as a variable is Stock Price, Net Profit (Net Profit), Liabilities, Capital, Sales, EBT and Size Asset). The data used is a period of 9 years, long time data is to be able to find better results of research than a period of only a few years. The findings of this study, Variable Liabilities have a significant effect on stock prices, Variable Capital has no significant effect on stock prices, Variable Sale significant effect on stock prices, EBT variables have a significant effect on stock prices, Profit variables have no significant effect on stock prices. Keyword : Liabilities, Sale, Capital, EBT, Profit, Stock Price